Pyrolysis of palm pressed fibre (PPF) toward maximizing Bio-Oil yield in a Fixed Bed Reactor - Muhammad Hisyamuddin Shahrin (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Palm Pressed Fiber (PPF) is the by-products during oil-palm processing. Pyrolysis of PPF was investigated toward maximizing bio-oil yield in a fixed-bed reactor. Two series of the PPF pyrolysis experiments were conduct to determine the effects of temperature and heating rate on pyrolysis yield. The nitrogen flow rate was constant at 100 cm3/min. The first series of experiments was conduct to determine the effect of pyrolysis temperature on the pyrolysis products yield at varied temperature range from 300, 400, 500, 600 and 700 °C . The second series of experiment was conduct using the optimum bio-oil yield pyrolysis temperature with the heating rate varied at 10, 20, 30, 40 and 50 °C /min. The optimum pyrolysis temperature and heating rate yield for the PPF pyrolysis was at 500 °C and 30 °C /min where the highest bio-oil yield of 45.05 % was obtained with bio-char yield of 31.47 % and 23.48 % gas produced. The kinetic study of thermal degradation of PPF was studied using Ozawa model. The activation energy, EA was 135.738 mol-1.